Mobile Cloud Computing: Security Levels, Challenges and Applications - Rajak, Nidhi; Shukla, Diwakar (International Journal of Computer Sciences and Engineering, 2025)
Due to the advancement of mobile technology and its low cost, mobile telephony has been penetrated at large level. Smartphone users are growing with a rapid pace and the number of new research dimension has been emerged in mobile computing. Mobile Cloud Computing (MCC) is one of the burning areas of research in computer science. it is basically the combination of cloud computing and mobile computing. Availability of high speed internet and enhancement in the battery life of mobile devices, the usage of internet over mobile phone has been increased. In this study, a brief definition of cloud computing, mobile computing and mobile cloud computing is presented. After that a deliberated discussions on MCC architecture, different security levels, and challenges of MCC are covered. At last some applications are discussed where MCC is commonly used.